The center of topologically primitive exponentially galbed algebras - Mart Abel; Mati Abel (International Journal of Mathematics and Mathematical Sciences)
Let A be a unital sequentially complete topologically primitive exponentially galbed Hausdorff algebra over ℂ, in which all elements are bounded. It is shown that the center of A is topologically isomorphic to ℂ.